RESPONSE OF MUSTARD (BRASSICA JUNCEA L.) CZERNJ. & COSSON) TO POTASSIUM WITH OTHER NUTRIENTS ON YIELD AND QUALITY - PALIWAL, ARUNIMA; J. P. SINGH (The Bioscan, 2014)
A field experiment to evaluate response of mustard (Brassica juncea L.) Czernj. and Cosson) to potassium in combination with other nutrients on yield and quality was conducted at N. E. Borlaug Crop Research Centre of Govind Ballabh Pant University of Agriculture and Technology, Pantnagar (Uttarakhand) during rabi season of 2012-13. The experiment, comprising of twelve treatments was laid out in Randomized Block Design with three replications. The results revealed that higher seed yield per hectare (1817 kg ha-1) was obtained at 150% NPK due to higher values of yield attributing characters viz. number of siliquae per plant (324.5), length of siliqua (4 cm), 1000- seed weight (3.7 g) and seed weight per plant (13.9 g). Protein yield (306 kg ha-1) and oil yield (736 kg ha1) was also recorded maximum at 150% NPK level. Therefore, it can be concluded that application of 150% NPK should be used for improvement of yield and quality of mustard under tarai condition of Uttarakhand.